Pengaruh FDR, NPF dan CAR Terhadap Profitabilitas (ROA) Bank Syariah Yang Terdaftar di Bursa Efek Indonesia (Periode 2015-2019) - Ibrahim (Fakultas Syariah dan Ekonomi Islam, 2021)
This study aims to determine the effect of Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) and Capital Adequacy Ratio (CAR) on Return on Assets (ROA) in Islamic banking listed on the Indonesia Stock Exchange (period 2015-2019). This research uses descriptive quantitative method with multiple linear regression analysis tools. The results showed that the FDR, NPF and CAR ratios simultaneously affect the ROA of Islamic Banking. While the partial result, FDR, has a negative and insignificant effect on ROA, for the NPF ratio has a negative and significant effect on ROA. Furthermore, the CAR ratio has a positive and significant effect on the ROA of Islamic banking.